Initial Findings From Project Recover: Overcoming Co‐Occurring Eating Disorders and Posttraumatic Stress Disorder Through Integrated Treatment. Issue 2 (11th April 2017) - Trottier, Kathryn; Monson, Candice M.; Wonderlich, Stephen A.; Olmsted, Marion P.
Abstract : This pilot study is the initial investigation of an integrated cognitive behavioral therapy (CBT) for co‐occurring eating disorders (ED) and posttraumatic stress disorder (PTSD). Following a course of intensive hospital‐based ED treatment focused on ED behavioral symptom interruption, 10 individuals with ED‐PTSD received 16 sessions of CBT that focused on maintaining improvements in ED symptoms outside of the hospital environment and integrated cognitive processing therapy for PTSD. We hypothesized that the treatment would be associated with significant improvements in PTSD symptoms, depression, and anxiety, as well as sustained improvements in ED symptomatology. There were statistically significant improvements in clinician‐rated PTSD symptoms ( g av = 4.58), depression ( g av = 1.37), and anxiety ( g av = 1.00). As expected, there was no statistically significant change in ED cognitions ( g av = .28). Reliable change analyses revealed that only 1 participant experienced deterioration in ED cognitions over the course of the integrated treatment. Of the 9 participants who were remitted from behavioral ED symptoms at the end of intensive treatment/beginning of the integrated treatment, 8 remained behaviorally remitted at poststudy treatment, which is encouraging given the high rate of rapid relapse following intensive ED treatment. Findings from this study provide preliminary support for the efficacy of an integrated CBT for ED‐PTSD.